Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fpsyt.2020.588803
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Stress, Presenteeism, Absenteeism, and Resilience Amongst University Staff and Students in the COVID-19 Lockdown

Abstract: Background: This study explored how the COVID-19 outbreak and arrangements such as remote working and furlough affect work or study stress levels and functioning in staff and students at the University of York, UK.Methods: An invitation to participate in an online survey was sent to all University of York staff and students in May-June 2020. We measured stress levels [VAS-scale, Perceived Stress Questionnaire (PSQ)], mental health [anxiety (GAD-7), depression (PHQ-9)], physical health (PHQ-15, chronic medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
93
2
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(141 citation statements)
references
References 42 publications
(39 reference statements)
8
93
2
6
Order By: Relevance
“…This indicates that the relationship between resilience and stress is more complex than initially assumed and needs further investigation. In line with the results of the present research, the study by van der Feltz-Cornelis et al (2020) concluded that the promotion of resilience should not focus exclusively on stress, but rather address it from a multifactorial perspective, since the relationship is not as direct as one might think a priori. Additionally, it would be notable to introduce the variables depression and anxiety into the neural network model, since other studies have identified them to be closely related to stress (Rodríguez-Hidalgo et al, 2020), as well as develop an ANN whose dependent variable is the moment (pre-or post-confinement).…”
Section: Future Lines Of Researchsupporting
confidence: 85%
“…This indicates that the relationship between resilience and stress is more complex than initially assumed and needs further investigation. In line with the results of the present research, the study by van der Feltz-Cornelis et al (2020) concluded that the promotion of resilience should not focus exclusively on stress, but rather address it from a multifactorial perspective, since the relationship is not as direct as one might think a priori. Additionally, it would be notable to introduce the variables depression and anxiety into the neural network model, since other studies have identified them to be closely related to stress (Rodríguez-Hidalgo et al, 2020), as well as develop an ANN whose dependent variable is the moment (pre-or post-confinement).…”
Section: Future Lines Of Researchsupporting
confidence: 85%
“…Similar to the Feltz-Cornelis and colleagues' study and the study by Xiang and colleagues, our data suggested an association between low physical activity and low-clinical GA (Table 2). 28,29 However, contrary to these studies, we did not see any association between low physical activity and high-clinical GA. 28,29 Our study suggests that the protective effect of physical activity is limited to low-clinical GA but not high-clinical GA.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, the proportion of self-reported depression symptoms was 65.2%, where mild and M/S accounted for 53.7 and 11.5%, respectively. Our finding is higher than that of several online surveys conducted in the general population during the COVID-19 pandemic (17.2-37.1%) (6,31,32), and it is also higher than a study conducted in the UK among college students (46.5%) (33). Moreover, the mean score of self-reported depression was 54.8 ± 9.0, which is higher than the Chinese norm (41.88 ± 10.57) and a study conducted in Shandong, China (42.47 ± 8.61) (p < 0.05) (34).…”
Section: Discussioncontrasting
confidence: 86%